Qumranica minora - Garcia Martinez, Florentino. (Studies on the Texts of the Desert of Judah, 2007)
Qumranica Minora II: Thematic Studies on the Dead Sea Scrolls brings together fourteen previously published studies of Florentino Garca Martnez on a variety of thematic topics from the Dead Sea Scrolls, including English translations of essays that were hitherto only available in French or Spanish. The studies range from essays on the interpretation of the biblical texts in the Scrolls, to more general studies on topics such as priestly functions in a community without temple, Messianism, magic, wisdom, sonship between the Old and the New Testament, and the Ì€œotherÌ€ in the Dead Sea Scrolls or at Qumran.